Sonoelastographic Evaluation of the Lower Lateral Nasal Cartilage Lateral Crus, Auricular Conchal Cartilage, and Costal Cartilage - Şahan, Mehmet Hamdi; Bayar Muluk, Nuray; Inal, Mikail; Asal, Neşe; Şimşek, Gökçe; Arıkan, Osman Kürşat (Facial Plastic Surgery, 2019)
We investigated the sonoelastographic features of the lower lateral nasal cartilage lateral crus (LLNC-LC), auricular conchal cartilage (ACC), and costal cartilage (CC). In this prospective study, group 1 consisted of 60 participants (30 males and 30 females) between 18 and 35 years of age. Group 2 consisted of 60 participants (30 males and 30 females) between 35 and 50 years of age. Strain elastography (SE) and shear wave elastography (SWE) were performed. For all LLNC-LCs and ACCs, type I SE was detected more in group 2, type II SE was detected more in group 1, and type III SE was detected more in group 1 (p < 0.05). For CC, type I SE was detected more in both groups (p < 0.05). For LLNC-LC, type I SE was detected more in males compared with females in both groups (p < 0.05). For all LLNC-LC, ACC and CC, the SWE modulus of group 2 was significantly higher than that of group 1 (p < 0.05). In older participants, the SWE modulus increased. We recommend using ACC mainly in rhinoplasty operations for primary and revision cases as its SWE modulus is similar to that of the LLNC-LC. However, due to the higher SWE modulus of CC, CC grafts should not be used as the first choice in rhinoplasties, especially in the reconstruction of the nasal tip contour, but may be used in nasal dorsum augmentation.
Keywords: strain elastography; shear wave elastography modulus; lower lateral nasal cartilage lateral crus; auricular conchal cartilage; costal cartilage